Essential Elements to Guide Novice Professionals in the Design of an Orientation Model - Vargas Cordero, Zoila Rosa (2013)
This article is based on a class taught by the author in a Professional Development workshop addressed to students majoring in Counseling. The paper includes basic elements that must be taken into consideration to prepare the design of a work model, which should be used as the referent to guide the counseling process for interns as well as for new professionals. The article provides a general overview of each element in the design, including the importance of knowing the general philosophical framework of the Counseling field.  It briefly describes the step-by-step process to be followed from each theoretical and practical referent. In addition, it includes the ethics component required to promote the ethical performance of duties of every professional and the compliance with the code ruling the professional’s expected behavior. A brief review of the necessary attitude of professionals is included at the end as well as the role to be taken in the different areas. The article is aimed at offering novice professionals with a guide that will help them develop the expertise necessary to add an epistemological positioning to their practice.